Alterations in myocardial collagen content affect rat papillary muscle function - Matsubara, Luiz Shiguero [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Okoshi, Marina Politi [UNESP]; Cicogna, Antonio Carlos [UNESP]; Janicki, J. S. (Amer Physiological Soc, 2000)
We investigated the influence of myocardial collagen volume fraction (CVF, %) and hydroxyproline concentration (mu g/mg) on rat papillary muscle function. Collagen excess was obtained in 10 rats with unilateral renal ischemia for 5 wk followed by 3-wk treatment with ramipril (20 mg . kg(-1) . day(-1)) (RHTR rats; CVF = 3.83 +/- 0.80, hydroxyproline = 3.79 +/- 0.50). Collagen degradation was induced by double infusion of oxidized glutathione (GSSG rats; CVF 5 2.45 +/- 0.52, hydroxyproline = 2.85 +/- 0.18). Nine untreated rats were used as controls (CFV = 3.04 +/- 0.58, hydroxyproline = 3.21 +/- 0.30). Active stiffness (AS; g . cm(-2) . %L-max(-1)) and myocyte cross-sectional area (MA; mu m(2)) were increased in the GSSG rats compared with controls [AS 5.86 vs. 3.96 (P< 0.05); MA 363 +/- 59 vs. 305 +/- 28 (P< 0.05)]. In GSSG and RHTR groups the passive tension-length curves were shifted downwards, indicating decreased passive stiffness, and upwards, indicating increased passive stiffness, respectively. Decreased collagen content induced by GSSG is related to myocyte hypertrophy, decreased passive stiffness, and increased AS, and increased collagen concentration causes myocardial diastolic dysfunction with no effect on systolic function.
Keywords: renovascular hypertension; fibrosis; oxidized glutathione; active stiffness; passive stiffness